Analysis of factors affecting employee performance - Yusuf Ronny Edward; Nagian Toni; Erina Alimin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
A company's human resources are a significant asset for business growth. Performance of working employees determines how far a company advances. This study aims to examine the variables that affect employees' productivity at PT Z. This study uses a quantitative, SEM-PLS methodology. A questionnaire with a 1–5 rating scale was given to 56 randomly selected respondents, who provided the data. The software SmartPLS is then used to examine the data that has been gathered. The study's latent variables included employee performance, job happiness, work culture, and work experience. The findings demonstrated that the composite reliability and AVE values were both greater than 0.5 and 0.7, respectively. Everything created for the model, it can be said, has strong discriminant validity. Each item's loading factor value is more than 0.7, indicating that all the variables are legitimate. The job satisfaction variable in the hypothesis test had no impact on worker performance. Employee performance, meanwhile, is influenced by workplace culture and experience.